Oceanic mesoscale turbulence drives large biogeochemical interannual variability at middle and high latitudes. Issue 7 (7th April 2014) - Lévy, Marina; Resplandy, Laure; Lengaigne, Matthieu
Abstract : Observed phytoplankton interannual variability has been commonly related to atmospheric variables and climate indices. Here we showed that such relation is highly hampered by internal variability associated with oceanic mesoscale turbulence at middle and high latitudes. We used a 1/54° idealized biogeochemical model with a seasonally repeating atmospheric forcing such that there was no external source of interannual variability. At the scale of moorings, our experiment suggested that internal variability was responsible for interannual fluctuations of the subpolar phytoplankton bloom reaching 80% in amplitude and 2 weeks in timing. Over broader scales, the largest impact occurred in the subtropics with interannual variations of 20% in new production. The full strength of this variability could not be captured with the same model run at coarser resolution, suggesting that submesoscale resolving models are needed to fully disentangle the major drivers of biogeochemical variability at interannual time scales. Key Points: Submesoscales generate interannual variations in phytoplankton blooms The variability occurs at local scale and translates to larger scale High horizontal resolution is needed to fully capture it